Using Local Plant Remains to Get Rid of Ammonia Nitrogen from Well Water in Wadiderna (Libya) after Hurricane Daniel - Hanan Khalifa; Waleed Ramadhan (AlQalam Journal of Medical and Applied Sciences, 2024)
A "hotspot" for research in recent years has been the mechanism of ammonia nitrogen removal from black and odorous water, particularly during the phytoremediation process. Since ammonia is thought to be a source of water pollutants and harmful to the health of city residents, the effectiveness of adsorption and removal of ammonia in Derna, Libya's groundwater was investigated. Native plants with a reputation for adsorption were chosen. These included animal remnants like charcoal and pomegranate peel. The findings demonstrated the efficiency of activated charcoal made from residues. Ammonia is eliminated by urban vegetation. In terms of adsorption capacity and ammonia-to-groundwater pollution removal, Almond Peel Activated Charcoal "APAC" outperformed Pomegranate Peel Activated Charcoal "PPAC". It is concluded that ammonia in surface and subsurface water can be treated using the "APAC" by adsorption. أصبحت آلية إزالة النيتروجين الأمونيا من المياه السوداء والروائح "BOW" موضوعاً بارزاً للبحث في السنوات الأخيرة، خاصة خلال عملية المعالجة النباتية.ونظرا لخطورة الامونيا على الحياة البشرية والحيوانية اجريت هذه الدراسة بعد اعصار دانيال وبالتحديد خلال الموسم الزراعي 2023-2024م لتقييم تأثير بقايا بعض النباتات خاصة الرمان والجوز (عين الجمل )على امتصاص الامونيا من مياه وادي درنة ،وبينت النتائج فعالية الفحم النشط المصنوع من مخلفات النباتات المحلية في المدينة في إزالة الأمونيا؛ فقد تفوق "APAC" على "PPAC" في قدرة الامتصاص وإزالة ملوثات المياه الجوفية من الأمونيا؛ وخلص إلى أن "APAC" يمكن استخدامه في علاج الامتصاص للأمونيا في المياه الجوفية والسطحية.